Pengaruh Kualitas Pelayanan dan Fasilitas Terhadap Kepuasan Tamu di Hotel Blue Karma Seminyak - Dewi, Ni Made Diana Yunita; Widiantara, I Gusti Agung Bagus; Widyaningsih, Ni Putu Putri (Universitas Triatma Mulya, 2025)
The growth of tourism in the Seminyak area of Bali has had a significant impact on the increase in hotel occupancy, including Hotel Blue Karma Seminyak. However, mixed guest reviews indicate an imbalance between expectations and reality of the services and facilities provided. This study aims to analyze the effect of service quality and facilities on guest satisfaction partially and simultaneously, and identify the dominant variables that affect satisfaction. This study uses a quantitative approach with a survey method through a closed questionnaire to 90 respondents selected by purposive sampling. Data analysis was carried out using validity, reliability, classical assumption, multiple linear regression, t test, F test, and coefficient of determination. The results showed that both service quality and facilities had a positive and significant effect on guest satisfaction. The service quality variable has a dominant influence with the highest standardized beta value (0.423), compared to facilities (0.389). Simultaneously, both variables were able to explain 50.8% of the variation in guest satisfaction. This finding confirms the importance of improving aspects of service and facilities to build an optimal stay experience.